Crisis communication in a natural disaster: a chaos theory approach - Purworini, Dian; Purnamasari, Dini; Hartuti, Desy Puji (Penerbit Universiti Kebangsaan Malaysia, 2019)
Various studies indicated the need for crisis communications in natural disasters because a disaster can trigger crisis. Disasters that occur in remote areas need a strategised approach and tailored communication plan to suit with the characteristics of the local community. This research uses chaos theory to describe crisis communication and analyses the role of communications during floods in the Klaten region in Indonesia. Flood is often struck in this area. The concepts of chaos theory are analysed during this disaster, such as guidance on the initial conditions, the shock of the situation, the changes of the existing system, and the emergence of a helper. In-depth interviews were conducted with 14 informants from residents in two sub-districts of Klaten and 4 staff in the disaster menagement district office Klaten region (BPBD). The results indicated that although the same catastrophic pattern is observed, people still find it shocking everytime. It was also observed that ideas or strategy to deal with the flood are made spontaneously following the disaster, often in an urgent state. The role of the helper is also very memorable for the community. The communication channel used are informal, face to face and utilising traditional channels. The ability of social media has not been employed by the villagers, particularly the older generation, nevertheless the younger generation could still explore this platform during crisis. Future research can evaluate another important field that appears to be important in disaster communication, which is public diplomacy. This hopefully could explore more asumptions of the chaos theory during disaster.